Effectiveness of Using A Combination of Rice Husk Ash and Monosodium Glutamate (MSG) on Growth of Lettude Plant (Lactuca sativa L.) - Sari, Leli Mustika; Rahmadina, Rahmadina; Idris, M. (Jurnal Biologi Tropis, 2024)
Lettuce is a plant that is quite popular with the public. Not only does it have economic value but it also has quite high nutritional content. So one method used to maintain the stability of lettuce production on the market is by providing rice husk ash and monosodium glutamate (MSG). This research uses a non-factorial randomized block design (RAK) which consists of 5 levels, namely giving fertilizer without combination and giving combined fertilizer, namely P1 (Rice husk ash 100 grams/polybag), P2 (MSG 15 grams/polybag), P3 (Combination of rice husk ash and MSG with a dose ratio of 100 grams of rice husk ash : 15 grams of MSG), P4 (Combination of rice husk ash and MSG with a dose ratio of 75 grams of rice husk ash : 10 grams of MSG), P5 (Combination of rice husk ash and MSG with a dose ratio of 50 grams of rice husk ash: 5 grams of MSG). The study's findings demonstrated a significant impact on all parameters (plant height, number of leaves, leaf area index, and plant fresh weight) when a combination of rice husk ash and MSG was used. The results of testing the levels of chlorophyll a b and the total use of a combination of rice husk ash and MSG did not provide a significant effect. The most effective dose to increase the growth of lettuce plants was the use of a combination of rice husk ash and MSG with a level of P3 = 100 grams of rice husk ash: 15 grams of MSG.